(untitled) (Texas Journal of Medical Science, 2026)
Menstrual rhythm disturbances during puberty often reflect a combination of neuroendocrine immaturity and early forms of ovulatory dysfunction. In the context of abnormal body weight, inflammatory mechanisms may serve as an additional factor modulating reproductive regulation